Analisis Kebutuhan Perencanaan Karir Berbasis Aspirasi Karir Mahasiswa:Studi Literatur - Pratiwi, Tiara Iskandar; AS, Uman Suherman; Supriatna, Mamat; Nadhirah, Nadia Aulia (Indonesian Journal of Educational Counseling, 2024)
Career aspirations motivate students to form a vision of their professional future, provide direction in selecting relevant education and experiences, and to continue to grow personally and professionally. This study aims to review the analysis of student career needs based on theoretical student career aspirations. The method used is a systematic literature review. The results of the literature review recommend further research for research on 1) factors that influence the formation of career aspirations; (2) the relationship between career aspirations and job satisfaction; (3) differences in career aspirations between demographic groups such as gender, age, educational background, or ethnicity; (4) the impact of career aspirations on motivation and work involvement; (5) the role of education in forming career aspirations; (6) comparison of career aspirations between different cultures or countries